Respuesta :
Answer:
[tex] {x}^{2} + 9[/tex]
Step-by-step explanation:
[tex] {(x + 3)}^{2} - 6x \\ \\ = {x}^{2} + {3}^{2} + 2 \times x \times 3 - 6x \\ \\ = {x}^{2} + 9 + 6x - 6x \\ \\ = {x}^{2} + 9[/tex]
Answer:
The answer is x² + 9.
Step-by-step explanation:
First, you have to get rid of bracket of square :
[tex] {(a + b)}^{2} \: ⇒ \: {a}^{2} + 2ab + {b}^{2} [/tex]
[tex] {(x + 3)}^{2} [/tex]
[tex] = (x + 3)(x + 3)[/tex]
[tex] = {x}^{2} + 6x + 9[/tex]
Next, you can simplify :
[tex] {x}^{2} + 6x + 9 - 6x[/tex]
[tex] = {x}^{2} + 9[/tex]